THE EFFECT OF FLOOD ON THE SOCIO-ECONOMIC ACTIVITIES ON RESIDENT OF ASABA, DELTA STATE - Egbuna, Onyinyechi; Eyare, Ewa Raymond (FUDMA Journal of Sciences, 2026)
Flooding has become a recurrent environmental and urban planning challenge in Asaba, Delta State, Nigeria, with significant implications for socio-economic activities and urban sustainability. This study examined the effects of flooding on socio-economic activities in Asaba with particular emphasis on drainage deficiencies, blocked waterways, weak planning enforcement, and floodplain encroachment. A mixed-method research design was adopted using questionnaires, interviews, and field observations. A total of 400 questionnaires were distributed across flood-prone communities, while 372 valid responses were retrieved and analyzed using descriptive statistics and thematic analysis. Findings revealed that 84.1% of respondents experienced flooding annually, while 85.5% identified inadequate drainage infrastructure as the major cause of flooding. Other significant drivers included blocked drainage channels (80.9%), uncontrolled urban development (72.3%), and floodplain encroachment (68.3%). The study further showed that flooding severely disrupts transportation (88.2%), damages residential properties (84.4%), reduces business income (79.6%), affects agricultural production (69.3%), and contributes to temporary displacement and school disruption. Spatial evidence indicated that riverbank and low-lying communities were the most vulnerable due to poor drainage connectivity and weak development control. The study concludes that flooding in Asaba is not only a climatic issue but also a consequence of inadequate urban planning and infrastructure management. The study recommends prioritizing drainage rehabilitation, strengthening waste management systems, enforcing floodplain-sensitive development regulations, improving early warning compliance, and enhancing institutional coordination for effective urban flood risk management and sustainable urban resilience in Asaba.
Keywords: Flooding; Urban Planning; Socio-Economic Activities; Drainage Infrastructure; Flood Risk Management; Urban Resilience; Disaster Risk Reduction; Asaba; Floodplain Encroachment; Nigeria